Bentuk Kegiatan Gotong Royong Dalam Aspek Pertanian Dan Sosial Budaya Di Kabupaten Muna (Studi Kasus di Desa Langkoroni Kecamatan Maligano Kabupaten Muna) - Sinaini, La; Iwe, La (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
The purpose of this study was to determine the forms of mutual assistance activities in the aspects of agriculture and socio-culture in Langkoroni Village, Maligano Sub District, Muna Regency. This research was conducted in August 2019 until January 2020. This research method uses qualitative methods. Sources of data in this study used informants. The results of the research show mutual cooperation activities in the aspects of agriculture, namely clearing farmland, fencing farmland, planting, weeding, and harvesting. Mutual cooperation in the aspect of agriculture occurs because of feelings of help and a feeling of family. Mutual cooperation in the socio-cultural aspects, namely (1) community social cooperation such as marriages, house construction, Islamic events, seclusion, celebrations of Islamic holidays, and ceremonies of death. Mutual cooperation in the socio-cultural aspects occurs not only because of feelings of help and a feeling of family, but also a feeling of worship. Mutual cooperation in the aspect of agriculture is more focused on strengthening the family's economy and sense of kinship, while mutual cooperation activities in the socio-cultural aspect are more emphasized on a sense of kinship and the embodiment of worship.